American English in Hotels: A Sociolinguistic Observation and Analysis - Nida, Khoirin; Ardianto, Ardik (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2025)
In the global hospitality industry, English plays a crucial role as a lingua franca to facilitate communication between diverse international personnel and guests. Although English exists in various accent varieties worldwide, initial observation within the context of hotels in Indonesia indicates a tendency towards the dominant use of English with an accent resembling American English (AE). This study aims to explore this phenomenon by identifying the linguistic characteristics of the observed accent and analyzing the underlying sociolinguistic factors. Employing a descriptive-qualitative approach based on observation and literature review, it incorporates a linguistic analysis of prominent AE pronunciation features, as well as a sociolinguistic analysis relating to external influences. Findings indicated that the accent used by personnel displays the characteristic of AE features, such as rhoticity and certain vowel patterns. Further analysis suggested that the prevalence of this accent is significantly influenced by extensive exposure to American English through mass media—a positive perception of such variety regarding comprehensibility and professional image as well as the potential influence of American English models in hospitality training materials. Albeit facing challenges of accent diversity in the multilingual environment, the tendency towards AE accent reflects the complex dynamics in the use of English as a lingua franca in the service sector shaped by the convergence of sociocultural and pedagogical factors.